Hackneying hybridity? Fending off 'foreignness', Khoja Community and hybridisation in The Magic of Saida - Bhat, Shilpa Daithota (2019)
In the context of colonialism, religion and culture, the theory of cultural hybridity has assumed paramount importance due to its ineluctable nature. However, as most critics and theorists have suggested, the concept gestures at the precedence and prior existence of purity and this perception is exceedingly contentious. This article examines the various layers of hybridisation, Khoja Community (specifically Ismaili faith) and the complexities that it inherently contains and focuses on the argument that while Hybridity is contestable due to its ever-shifting connotations and inherent ambiguity, the so-called 'differences' in textual representation, culture and religion, actually move forward towards a homogenous state. To study the subject, the study focuses on the narrative, The Magic of Saida, by M. G. Vassanji. Like his trajectory through continents, his characters too traverse the oceans, and explore in new lands through the forces of acculturation and hybridisation. Despite, the seemingly forces of admixture, what is palpable is the ability of readers to discern the 'differences' in the intermixed format. If the differences are ostensible in hybridised version, can the resulting creation be called hybridised? This paper investigates this idea and is premised on how the theory is self-contradicting.
Keywords: Imperialism; Khoja community; M. G. Vassanji; The Magic of Saida; hybridisation